Adsorption Isotherms for CBY 3G-P Dye Removal from Aqueous Media Using TiO2 Degussa, Fe2O3, and TiO2/(DPC) - Shireen Abdulmohsin Azeez; Fadhela Muhammad Hussein; Rasha Wali Mohi Alsaedi (Universitas Gadjah Mada, 2023)
The adsorption of Cibacron Brilliant Yellow (CBY) 3-GP dye onto TiO2 Degussa, Fe2O3, and TiO2 anatase/Diphenylcarbizide in aqueous solution was studied with respect to temperature, contact time, and pH. The CBY 3-GP adsorption at equilibrium increased as the initial dye concentration increased for TiO2/DPC, while it decreased for TiO2 Degussa; however, it increased the initial dye concentration. The best removal efficiency was obtained at 1 mg for TiO2/DPC, TiO2 Degussa, and the amount of adsorption decreases with the rising of temperature. The negative ΔH° reveals the adsorption is exothermic and extremely negative ΔS° for TiO2 Degussa. The negative value for ΔS° indicates a regular increase of the randomness at the TiO2/DPC and Fe2O3 solution interface during adsorption. The intraparticle diffusion, pseudo-first- and second-order kinetic models were used. The Langmuir, Temkin, Freundlich, and Dubbin adsorption models were examined to describe the equilibrium isotherms. The usage of TiO2 Degussa and TiO2/DPC indicates that the equilibrium sorption was favorable.